Transformación Del Sector Eléctrico Mexicano, Obstáculos Y Perspectivas De Competitividad Global En 2016 - Vilchis Vidal, Agustín; Aranda Pastrana, Elsa (European Scientific Journal, ESJ, 2016)
This paper discusses the transformation of Mexico's electricity sector at birth as a parastatal entity of the federal government in 1937, until it became a productive state enterprise in 2016. In this transit, a series of obstacles can be seen that define its insertion in a global energy environment complex, dynamic, and very competitive. The work method was mixed descriptive and longitudinal between 2008 and 2016, the assessment is based on national and international indicators of energy efficiency, fuel use, energy diversification, and human resources, as well as interviews with experts to learn about the competitive prospects of the sector. The results show that the productive state enterprise outstanding large cargo, such as labor liabilities, debts incurred in dollars and with variable interest rate, all affect their levels of competitiveness in an international and national environment. However, the accumulated knowledge of its technical staff, a culture of solid quality, diversification of its energy portfolio, coupled with a comprehensive infrastructure of power plants and the transmission network, envision scenarios that, if properly managed, can allow strategic alliances for cogenerate value in the electricity sector and can improve the competitiveness and sustainability indicators. However, it should also be mentioned that the exogenous context is unfavorable with a tendency to systematically reduce CFE’s participation in the domestic market.